Optimalisasi Kearifan Lokal Indonesia Melalui Sosialisasi dan Latihan Pencak Silat Tapak Suci pada Siswa SB Hulu Langat Selangor Malaysia - Jamaludin; Hadiana, Oman; Hermawan; Nur, Hana Astria; Heriyana, Tio (Jurnal Pengabdian Tri Bhakti, 2024)
Community service activities carried out by the PTMA Muhammadiyah University Kuningan KKN-KI team present knowledge sharing through programs for the community in the Sanggar Bimbingan (SB) Hulu Langat, Selangor, Malaysia, especially for teachers and students. The aim of this service activity is to carry out a program to socialize local Indonesian wisdom through Pencak Silat Tapak Suci training based on the analysis results and objectives of KKN students. This community service activity method uses the focus group discussion (FGD) method both internally as a community service team and with residents of Sanggar Guidance Hulu Langat. The results of the activities of this program are Pencak Silat Tapak Suci training which includes stance training and basic moves.